Danger of digital drugs: prevention and control mechanisms - Saliha Laggoun; Zakhroufa Latreche (Social Empowerment Journal, 2023)
Through this study, we aim to search for the dangers of digital drugs, which have become considered among the deviant phenomena created in societies as a result of technological developments. Using earphones for each ear has a different frequency, which results in a change in the brain’s electricity and has the effect of using traditional drugs and revealing the difference between digital drugs and traditional drugs and the causes and risks. Efforts between civil society, governmental institutions, and social upbringing institutions, enacting deterrent laws to prevent their spread, and activating electronic protection programs.